EFFECTIVENESS OF ECOLOGICAL SANITATION FROM THE VIEWPOINT OF URINE APPLICATION ON VEGETABLES IN CENTRAL NEPAL - KC, Sharda; Shinjo, Hitoshi (MATTER: International Journal of Science and Technology, 2017)
Ecological sanitation can be defined as water conserving and nutrient recycling system for use of human urine and excreta in agriculture. In Nepal, every year 180 thousand ton of chemical fertilizer were imported. Ecological sanitation would count a lot to utilize locally available resources, to regenerate soil fertility, and to save national currency. The study was carried out at District, Nepal from March – August, 2016 to test the efficacy of human urine for improving crop performance and to estimate the feasibility of ecological sanitation. Five eco-san toilets were constructed and questionnaire survey was done. Villagers were asked about socio-economic parameters, farming practices, awareness of ecological sanitation and fertilizer value of urine. Eighty three percent respondents were engaged in agriculture growing mainly vegetables, which may raise the feasibility of ecological sanitation. Their concern on water deficiency in dry season, high demand of chemical fertilizer, sanitation awareness need to be solved. In the field experiment, cauliflower was cultivated to compare the fertilizer value of urine with chemical fertilizer and no fertilizer with three replications. Urine fertilized plots produced similar yields compared to those with chemical fertilizer and higher yields than those without fertilizer. To be able to generalize this conclusion, it is important to conduct experiments with different seasonal crops.